(untitled) (Archives of Mechanics - Test, 2011)
In the present paper, simulation results of stationary and propagating cracks in piezoelectric test specimens are presented. The simulations have been carried out with a self-developed adaptive finite element computer program. Two specimen configurations are investigated, i.e. the compact tension and three-point bending specimens. In the analysis of the propagating crack in the compact tension specimen, the fracture toughness change due to the change of the electric field in the test domain is taken into account. To prove the importance of the fracture toughness anisotropy assumption, crack growth simulations for the three-point bending specimens are reported.